2022
DOI: 10.1177/1179173x221114799
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Smoking on SARS-CoV-2 Positivity: A Study of a Large Health System in Northern and Central California

Abstract: Introduction COVID-19 continues to impact vulnerable populations disproportionally. Identifying modifiable risk factors could lead to targeted interventions to reduce infections. The purpose of this study is to identify risk factors for testing positive for SARS-CoV-2. Methods Using electronic health records collected from a large ambulatory care system in northern and central California, the study identified patients who had a test for SARS-CoV-2 between 2/20/2020 and 3/31/2021. The adjusted effect of active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(41 reference statements)
1
0
0
Order By: Relevance
“…Nevertheless, regarding SARS-CoV-2 and smoking, the information is unclear. A similar result was found in California, where a significantly low-risk level for SARS-CoV-2 positivity was found ( 42 , 43 ); Kashyap et al suggest that a possible explanation could be a weak immune response and large and deep deliberate exhalations, which expel large quantities and concentrations of viral particles ( 44 ). Other possible mechanisms have been reviewed by Shariq-Usman et al, which include low production of pro-inflammatory cytokines, local vasodilatation, low expression of ACE2, and high production of nitric oxide; however, the authors recommend that this information should be taken with caution since several biases and knowledge gaps were identified ( 45 ), and it was demonstrated that smokers have a worst diseases prognosis at the time of infection ( 46 , 47 ).…”
Section: Discussionsupporting
confidence: 63%
“…Nevertheless, regarding SARS-CoV-2 and smoking, the information is unclear. A similar result was found in California, where a significantly low-risk level for SARS-CoV-2 positivity was found ( 42 , 43 ); Kashyap et al suggest that a possible explanation could be a weak immune response and large and deep deliberate exhalations, which expel large quantities and concentrations of viral particles ( 44 ). Other possible mechanisms have been reviewed by Shariq-Usman et al, which include low production of pro-inflammatory cytokines, local vasodilatation, low expression of ACE2, and high production of nitric oxide; however, the authors recommend that this information should be taken with caution since several biases and knowledge gaps were identified ( 45 ), and it was demonstrated that smokers have a worst diseases prognosis at the time of infection ( 46 , 47 ).…”
Section: Discussionsupporting
confidence: 63%